Frequencies and Predictors of Negative Effects in Routine Inpatient and Outpatient Psychotherapy: Two Observational Studies - Gerke, Leonie; Meyrose, Ann-Katrin; Ladwig, Inga; Rief, Winfried; Nestoriuc, Yvonne (Frontiers in Psychology, 2020)
Negative effects of psychotherapy include side effects, malpractice, and unethical behavior. Its' setting-specific frequencies and predictors are mostly unknown. The aim of the two presented studies is to investigate NEP and its predictors systematically across different treatment settings. In study 1, N=197 patients of a German outpatient center were recruited on average 3.76 years after termination of psychotherapy. In study 2, data from N=118 patients of two German inpatient clinics were collected at admission (t0), discharge (t1), and 9-months follow-up (t2). All participants evaluated negative effects of their previous out-or inpatient psychotherapy and a priori hypothesized predictors. Inpatients reported significantly more side effects (U = 14347, z = 4.70 p < .001, r = 0.26) and malpractice and unethical behavior (U = 14168, z = 5.21, p < .001, r = 0.29) than outpatients. At least one side effect was reported by 37.3% of inpatients (t2) and 15.2% of outpatients. Frequently reported side effects were "experiencing more downs since the end of my therapy" by inpatients (t2; 16.1%) and "having trouble finding insurance or being worried about applying for new insurance" by outpatients (4.6%). At least one case of malpractice and unethical behavior was reported by 28.8% of inpatients (t2) and 7.1% of outpatients. Frequently reported cases were "being hurt by what the therapist said to me" by inpatients (t2; 20.3%) and "feeling forced to do things I did not want to do (e.g. confrontations, role plays)" by outpatients (4.1%). Rates of severe malpractice in form of breaking confidentiality, physical and sexual abuse were less than 1% in both settings. Predictors of side effects were prior experience with psychotherapy and current interpersonal difficulties. Predictors of malpractice and unethical behavior were a poor therapeutic alliance and prior negative experience with malpractice and unethical behavior. Negative effects of psychotherapy are common in both, in-and outpatient settings. Inpatients are at higher risk for negative effects of psychotherapy than outpatients. In order to safeguard patients' wellbeing, the systematic assessment and distinction of side effects and malpractice and unethical behavior should gain more attention in research and clinical practice.